Effects of Cognitive Apprenticeship and Critical Exploration Teaching Strategies on Basic Science Students’ Learning Outcomes in Selected Secondary Schools in Osun State, Nigeria (2015)
Records have shown low students‘ achievement in basic science; a trend which has been attributed to the use of conventional strategy (CS). This has necessitated the use of other innovative activity-based teaching strategies such as cognitive apprenticeship and critical exploration that could facilitate the teaching and learning of the subject. Previous studies have not considered the extensive use of these two strategies in improving learning outcomes in the subject. This study, therefore, determined the effects of Cognitive Apprenticeship Strategy (CAS) and Critical Exploration Teaching Strategies (CES) on students‘ learning outcomes in basic science in Osun State. It also examined the moderating effects of gender and parental supportiveness.The study adopted a pretest-posttest control group, quasi-experimental design with a 3x2x2 factorial matrix. Three Local Government Areas (LGAs) were randomly selected from Osun West senatorial district. Three co-educational schools with basic science teachers and laboratories were purposively selected from each of the LGAs while one arm of basic science Junior Secondary School II class from each of the nine schools was selected. Participants were randomly assigned to CAS (90), CES (90) and control (CS) (90) groups, while treatments lasted 12 weeks. The instruments used were: Basic Science Student Achievement Test (r=0.81), Student Basic Science Attitude (r=0.86), Student Basic Science Process Skills Rating (r=0.83) and Parental supportiveness (r=0.75) scales, Evaluation Sheet for Assessing Research Assistants‘ Performance, and Teachers Instructional guides on CAS, CES and CS. Seven hypotheses were tested at 0.05 level of significance. Data were subjected to analysis of covariance and Duncan post-hoc test.There was significant main effect of treatment on students‘ achievement in basic science (F (2,257)=66.56; ῆ2=.34). The students in CAS (x=13.35) performed better than those in CS ( x =7.90) and those in CES ( x =13.23) also performed better than those in CS ( x =7.90). Treatment had significant main effect on students‘ attitude to basic science (F(2,257)=3.59;ῆ2=.03). Participants in CAS had the highest adjusted mean score ( x = 37.44) than those in CES ( x = 37.21) and CS ( x = 35.20) groups. Treatment had significant main effect on science process skills (F (2,257) =3.35; ῆ2=.03). Participants in CAS ( x =21.28) had better posttest science process skills than those in CES ( x = 19.90) and CS ( x =19.53). Parental supportiveness had no significant main effect on achievement. Gender also had no significant main effect on achievement There was significant two-way interaction effect of treatment and gender on students‘ attitude to basic science (F (2,257) = 3.49). The best performance came from CAS male students ( x = 37.67) while the least performance came from CS male students ( x = 37.19). There was no significant three-way interaction effect of treatment, gender and parental supportiveness on students‘ achievement in basic science (F (2,257) = 1.32). Cognitive apprenticeship and critical exploration teaching strategies improved junior secondary school students‘ performance in basic science. These two strategies should be adopted for the improvement of students‘ learning outcomes in basic science; particularly male students with low parental supportiveness